Dominik Penn, Lexicographer at the Intersection of Slovenian and Greek - Matej Hriberšek (Keria: Studia Latina et Graeca, 2020)
Although the Slovenian language is relatively small, Slovenian lexicography has quite a rich history and tradition reaching right back to the 16th century. Until the 19th century, writers who made dictionaries and collections of Slovenian vocabulary prepared a fair amount of admirable works, albeit many remained in manuscript and have never been printed. In the 19th century, the study of the Slovenian language, efforts to preserve it, and the collecting of Slovenian linguistic material spread outside the central Slovenian land of Carniola; in Styria in particular, young intellectuals from those parts, such as Leopold Volkmer (1741–1816), Janez Krstnik Leopold Šmigoc (1787–1829), Peter Dajnko (1787–1873), Anton Krempl (1790–1844), and others, provided for the collecting of linguistic material alongside their literary endeavours; one of them was Friar Minor Dominik Penn. He was a fascinating lexicographer who included Greek in his work in a very unusual way.